Genetic analysis of bacteriophage N4 adsorption. - Kiino, D R (1989)
We isolated six mutants of Escherichia coli K-12 that were defective in bacteriophage N4 adsorption. We mapped the mutations to four loci designated nfrA through nfrD (N four resistance). nfrA and nfrB were tightly linked to each other and were mapped to min 12 of the E. coli linkage map. nfrC was mapped to min 85, and nfrD was mapped between min 44 and 58. We isolated a clone carrying both nfrA and nfrB and identified its gene products through maxicell analysis of plasmid subclones. The nfrA gene product was an outer membrane protein of 96,000 apparent molecular weight, whereas nfrB encoded an inner-membrane protein of 69,500 apparent molecular weight. The nfrB1 mutation did not affect the export of the nfrA gene product to the outer membrane and did not affect the alkaline phosphatase activity of an nfrA-phoA fusion. We propose that nfrA encodes the structural receptor for N4 and that the nfrB gene product may be required for irreversible adsorption and injection of the phage genome and virion-encapsulated RNA polymerase through the inner membrane.